(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role of Alexandr Faynberg in the process of formation and development of modern poetry. The poet’s poetic style, artistic thinking, philosophical reflections and innovations introduced into uzbek literature through lyrical imagery are highlighted. The study scientifically demonstrates how Faynberg’s poetry created a bridge between national traditions and modern poetics, as well as how his works influenced in the 1960-1980-s. The article reveals how the poet expanded the artistic possibilities of Uzbek poetry through his choice of themes, work with poetic forms, and his distinctive style. IN addition, this article contributes to fostering readers’ interest in poetry. In particular, it serves as evidence of the historical development of modern poetry.